Álcool, fumo e problemas periodontais em gestantes atendidas no sistema público de saúde - Santos, Renata Reis dos [UNESP]; Sundefeld, Maria Lucia Marçal Mazza [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (My University, 2012)
Objective: To analysis the presence of periodontal disease, smoking, alcoholic beverages consumption and the relation with many socioeconomic variables in pregnant women. Methods: It’s a crosssectional study where 119 pregnant women received prenatal. The interviews were performed at home or at public health centers using a semi-structured inquiry approaching questions about smoking, alcoholic beverages consumption, and socioeconomic data. Periodontal status was evaluated through IPC and PIP. Results: Among interviewed pregnant women, 26.88% confirmed ingestion of alcoholic beverages, smoking or the both habits. In relation to socioeconomic variables, 94.96% of them belong to C, D and E classes; 53.76% of pregnant women were unemployed; and 59.66% of total completed high school. The most prevalent periodontal status was presence of dental calculus (IPC=2). Conclusions: Alcoholic beverages consumption and smoking were some habits of pregnant women. It was observed no association between periodontal disease and smoking and alcoholic beverages.

Objetivo: O objetivo deste trabalho foi analisar a presença de doença periodontal, o uso de tabaco, consumo de álcool e a relação com variáveis socioeconômicas em gestantes. Metodologia: Trata-se de um estudo transversal no qual foram entrevistadas 119 gestantes que faziam o acompanhamento pré- natal. As entrevistas foram realizadas nos domicílios ou nas unidades de saúde, utilizando-se um formulário semiestruturado, abordando questões sobre o consumo de tabaco e álcool e dados socioeconômicos. Resultados: As condições periodontais foram avaliadas por meio do Índice Periodontal Comunitário (IPC) e do Índice Periodontal de Perda de Inserção (PIP). Das gestantes entrevistadas, 26,88% declararam utilizar álcool, fumo ou ambos. Em relação às variáveis socioeconômicas, 94,96% pertenciam às classes C, D e E; 53,76% estavam desempregadas; e 59,66% tinham ensino médio completo. A condição periodontal mais prevalente foi a presença de cálculo (IPC=2). Conclusão: A utilização de álcool e fumo foi encontrada entre gestantes. Não foi observada associação entre doença periodontal e uso de fumo e álcool.
Alcohol, tobacco and periodontal problems in pregnant women attended at public health system
Keywords: Pregnant women; Periodontics; Tobacco; Ethanol; Gestante; Periodontia; Tabaco; Etanol